Two-step enzymatic synthesis of ursodeoxycholic acid with a new 7β-hydroxysteroid dehydrogenase from Ruminococcus torques. Issue 4 (April 2015) - Zheng, Ming-Min; Wang, Ru-Feng; Li, Chun-Xiu; Xu, Jian-He
Highlights A new 7β-HSDH gene was cloned and its enzymatic properties were characterized. CDCA was transformed to UDCA using two enzymes with self-recycling of cofactor. By a two-step reaction strategy, the UDCA yield was improved up to 98%.